2003
DOI: 10.1007/s10152-003-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community in the tunic matrix of a colonial ascidian Diplosoma migrans

Abstract: This paper provides the first information on the morphology of different morphotypes of bacteria in the tunic matrix of the colonial ascidian Diplosoma migrans. Ascidians were collected from waters near Helgoland (German Bight, North Sea). The dominant type is represented by extremely high numbers of long, needlelike rods (length 10-30 m, width 0.5 m). The bacteria are motile by means of bipolar monotrichous flagella, generating swift sigmoidal movement. Bacteria are already present during different embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The bacterial spectrum in the developmental stages investigated is similar, except for A. butzleri and Flavobacterium sp. This suggests that intratunical bacteria are transferred from the tunic matrix to the offspring, which corresponds to microscopic observations (Groepler and Schuett 2003). The occurrence of vertical transfer of bacteria from the adult ascidian colony to its offspring is demonstrated by the DGGE profile (data not shown) of a fully developed larva, freed from the egg envelope and all bacteria of the perivitelline space, which shows a distinct main band.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The bacterial spectrum in the developmental stages investigated is similar, except for A. butzleri and Flavobacterium sp. This suggests that intratunical bacteria are transferred from the tunic matrix to the offspring, which corresponds to microscopic observations (Groepler and Schuett 2003). The occurrence of vertical transfer of bacteria from the adult ascidian colony to its offspring is demonstrated by the DGGE profile (data not shown) of a fully developed larva, freed from the egg envelope and all bacteria of the perivitelline space, which shows a distinct main band.…”
Section: Discussionsupporting
confidence: 79%
“…However, it is most likely that the main band (Rfa) (Fig. 2 shows 11 samples) corresponds to the extremely high numbers of the bipolarly monotrichously flagellated needle-like rods (Groepler and Schuett 2003). These rods were found exclusively inside the tunic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. didemni thus allows didemnid ascidians to thrive in nutrient-poor, light-rich environments of the tropics. Didemnids have also been found to contain other types of microbes, but unlike P. didemni, without extensive in vivo functional studies (21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Granulocytes with their clearance properties are critical components of innate immune response that involve specific mechanisms of recognition of pathogens to be eliminated. Previous studies have documented the presence of bacteria both inside the tunic and on the cuticle of Ciona (De Leo and Patricolo, 1980;De Leo et al, 1981;Groepler and Schuett, 2003) and cyanobacteria have been observed in the tunic from other ascidians (Hirose et al, 2006(Hirose et al, , 2009b. Recently, Blasiak and co-workers (2014) have analysed the intratunic resident bacterial communities.…”
Section: Discussionmentioning
confidence: 96%